The interdependence between developing and developed stock markets: the case of the Macedonian, Belgrade, Six Swiss and Euronext Paris Stock Exchange - Stevcevska Srbinoska, Dusica; Mrsik, Jadranka; Sekuloski, Egor; Nenovski, Tome (Serbian Journal of Management, 2021)
The aim of the paper is to examine the level of interdependence between developing and developed stock markets. The correlation of the Macedonian (MBI10) stock exchange index with the Belgrade (BELEX15), the Six Swiss (SLI) and the Euronext Paris (CAC40) stock exchanges from November 2005 to October 2018 was studied. In order to assess the impact of the crisis on the interrelations between these equity markets, the analyzed period was we subdivided into three segments (pre-crisis, during crisis and post-crisis) and the data sets were subjected to linear regression analysis. The research results indicate an increased correlation of the Macedonian with Belgrade and Euronext Paris Stock Exchanges and decreased correlation with Six Swiss during the time of financial distress comparing to pre and post crisis periods. The findings of this study contribute to the overall picture of the relationship between stock markets in the time of Financial Crisis. Moreover, by investigating the interrelationship between developing and developed European stock markets, the results suggest that financial market integration is time-varying.